2010
DOI: 10.1557/jmr.2010.0281
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of Ti/AlTiN/Ti-diamondlike carbon composite coatings on steel

Abstract: Ti/AlTiN/Ti-diamondlike carbon (DLC) composite coatings were deposited by midfrequency magnetron sputtering and Hall ion source-assisted deposition on high-speed steel W 18 Cr 4 V substrates. The coating microstructure and mechanical properties, including hardness, elastic modulus, coefficient of friction, and wear properties were investigated by scanning electron microscopy, Raman spectroscopy, scratch and ball-ondisk friction tests, respectively. Fairly smooth composite coating with strong interfacial adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…2 (a) and (b), DLC film deposition rates increased from 17 to 39 nm/min with an RF power increase from 20 W to 100 W, and to 45 nm/min with the pressure increase to 4 Pa. DLC films were deposited in a single cathode configuration, the conventionally used RF-PECVD method. It turns out that under the same deposition conditions, the deposition rate, obtained by a general RF-PECVD process, ranged from 4 to 10 nm/min [16], which is about one fourth of that achieved by a hollow cathode process. The degree of plasma ionization increased with the RF power and pressure, requiring a higher plasma density, which resulted in a higher deposition rate.…”
Section: Film Deposition Ratementioning
confidence: 90%
See 1 more Smart Citation
“…2 (a) and (b), DLC film deposition rates increased from 17 to 39 nm/min with an RF power increase from 20 W to 100 W, and to 45 nm/min with the pressure increase to 4 Pa. DLC films were deposited in a single cathode configuration, the conventionally used RF-PECVD method. It turns out that under the same deposition conditions, the deposition rate, obtained by a general RF-PECVD process, ranged from 4 to 10 nm/min [16], which is about one fourth of that achieved by a hollow cathode process. The degree of plasma ionization increased with the RF power and pressure, requiring a higher plasma density, which resulted in a higher deposition rate.…”
Section: Film Deposition Ratementioning
confidence: 90%
“…However, this method suffers from a low deposition rate, due to the low plasma density. In previous work, DLC films were prepared using PECVD with a deposition rate of 4-10 nm/min [16]. Z.…”
Section: Introductionmentioning
confidence: 99%
“…Mirosław Szala [20] et al found that with the increase of Al content, the adhesion of (Ti, Al)N film to substrate is higher, and (Ti, Al)N film showed better resistance to plastic deformation. In addition, Pang [21] et al found that the composite film formed by using (Ti, Al)N as the intermediate layer not only improved the bonding strength, but also enabled the stress to be effectively released to achieve the effect of wear resistance. Recently, Du [7] et al studied the Al 1−x Cr x N nano-multilayer film prepared by doping Al in CrN and found that as the grain size of the film increases, the interlayer interface coherence was destroyed, and the mechanical properties of the film also decrease.…”
Section: Introductionmentioning
confidence: 99%